Twenty-one days of spirulina supplementation lowers heart rate during submaximal cycling and augments power output during repeated sprints in trained cyclists - Gurney, T.; Brouner, J.; Spendiff, O. (Applied Physiology, Nutrition, and Metabolism, 2022)
Spirulina supplementation has been reported to improve time to exhaustion and maximal oxygen consumption (V?O2max). However, there is limited information on its influence over the multiple intensities experienced by cyclists during training and competition. Fifteen trained males (age 40 ± 8 years, V?O2max 51.14 ± 6.43 mL/min/kg) ingested 6 g/day of spirulina or placebo for 21 days in a double-blinded randomised crossover design, with a 14-day washout period between trials. Participants completed a 1-hour submaximal endurance test at 55% external power output max and a 16.1-km time trial (day 1), followed by a lactate threshold test and repeated sprint performance tests (RSPTs) (day 2). Heart rate (bpm), respiratory exchange ratio, oxygen consumption (mL/min/kg), lactate and glucose (mmol/L), time (seconds), power output (W), and hemoglobin (g/L) were compared across conditions. Following spirulina supplementation, lactate and heart rate were significantly lower (P < 0.05) during submaximal endurance tests (2.05 ± 0.80 mmol/L vs 2.39 ± 0.89 mmol/L and 139 ± 11 bpm vs 144 ± 12 bpm), hemoglobin was significantly higher (152.6 ± 9.0 g/L) than placebo (143.2 ± 8.5 g/L), and peak and average power were significantly higher during RSPTs (968 ± 177 W vs 929 ± 149 W and 770 ± 117 W vs 738 ± 86 W). No differences existed between conditions for all oxygen consumption values, 16.1-km time trial measures, and lactate threshold tests (P > 0.05). Spirulina supplementation reduces homeostatic disturbances during submaximal exercise and augments power output during RSPTs. Novelty: • Spirulina supplementation lowers heart rate and blood lactate during ~1-hour submaximal cycling. • Spirulina supplementation elicits significant augmentations in hemoglobin and power outputs during RSPTs.